The Temporal And Spatial Changes Of Beijing’s Pm 2.5 Concentration And Its Relationship With Meteorological Factors From 2015 To 2020 - Guo Peng; A. B. Umarova; G. S. Bykova (Geography, Environment, Sustainability, 2021)
Currently, Beijing is facing increasing serious air quality problems. Atmospheric pollutants in Beijing are mainly composed of particulate matter, which is a key factor leading to adverse effects on human health. This paper uses hourly data from 36 environmental monitoring stations in Beijing from 2015 to 2020 to obtain the temporal and spatial distribution of the mass concentration of particulate matter with a diameter smaller than 2.5 μm (PM2.5). The 36 stations established by the Ministry of Ecology and Environment and the Beijing Environmental Protection Monitoring Center and obtain continuous real-time monitoring of particulate matter. And the 36 stations are divided into 13 main urban environmental assessment points, 11 suburban assessment points, 1 control point, 6 district assessment points, and 5 traffic pollution monitoring points. The annual average concentration of PM2.5 in Beijing was 60 μg/m3 with a negative trend of approximately 14% year-1. In urban areas the annual average concentration of PM2.5 was 59 μg/m3, in suburbs 56 μg/m3, in traffic areas 63 μg/m3, and in district areas 62 μg/m3. From 2015 to 2020, in urban areas PM2.5 decreased by 14% year-1, in suburbs by 15% year -1, in traffic areas by 15% year-1, and in district areas by 12% year-1. The quarterly average concentrations of PM2.5 in winter andspring are higher than those in summer and autumn (64 μg/m3, 59 μg/m3, 45 μg/m3, 55 μg/m3, respectively). The influenceof meteorological factors on the daily average value of PM2.5 in each season was analysed. The daily average PM2.5 in spring, summer, autumn and winter is significantly negatively correlated with daily average wind speed, sunshine hours, and air pressure, and significantly positively correlated with daily average rainfall and relative humidity. Except for autumn, the daily average PM2.5 is positively correlated with temperature. Although Beijing’s PM2.5 has been declining since the adoption of the‘Air Pollution Prevention and Control Action Plan’, it is still far from the first level of the new ‘Ambient Air Quality Standard’(GB309S-2012) formulated by China in 2012.